A Fast and Efficient MPPT Technique Based on Voltage Transients for PV Systems Under Partial Shading Conditions - Celikel, Resat; Yilmaz, Musa (Inst Engineering Technology-Iet, 2025)
Obtaining maximum power from photovoltaic (PV) systems operating under partial shading conditions (PSC) is quite challenging. Maximum power point tracking (MPPT) algorithms are necessary to extract the maximum power from the PV system in a very short time with minimal error. In this study, a high-efficiency MPPT algorithm with fast tracking speed is proposed for PV systems operating under PSC. The proposed algorithm utilizes the charging behavior of the capacitor between the PV system and the DC-DC converter. The P-V curve of the PV system is obtained either when the system is initially energized or during the capacitor charging phase following discharge. The voltage corresponding to the maximum power point is then determined, and the PV system is operated at this voltage until a change in power is detected. The proposed method was tested on a 2 kW PV system modeled in the MATLAB/Simulink environment. Power outputs and tracking times were evaluated under six different challenging PSC scenarios. As a result of the simulations, the average efficiency across the six PSC cases was 99.678%, while the average tracking time was 0.013 s.
Keywords: maximum power point trackers; photovoltaic power systems